[PP.19.25] INCREASED CENTRAL PRESSURE AUGMENTATION IS ASSOCIATED WITH REDUCED SLEEP DURATION IN INDIVIDUALS EXPOSED TO AIRCRAFT NOISE POLLUTION: THE SERA-CV STUDY. (September 2017) - Bruno, R.; Faraguna, U.; Di Pilla, M.; Di Galante, M.; Banfi, T.; Gemignani, A.; Fidecaro, F.; Licitra, G.; Bonanni, E.; Berrettini, S.; Vigotti, M.A.; Taddei, S.; et al.
Abstract : Objective: Exposure to environmental noise might exert negative effects on cardiovascular function. Aim of the study is to explore whether sleep loss associated with exposure to aircraft noise has a detrimental effect on vascular function. Design and method: 22 individuals, heavily exposed (E) to aircraft noise (>50 DbA) were recruited and matched with a group of non-exposed individuals (NE). Pulse wave velocity (PWV), central blood pressure (BP), augmented pressure (AP) and augmentation index (Aix) were performed. 7-day actigraphy was performed for the assessment of total sleep time (TST) and wake after sleep onset (WASO). Results: E showed similar TST (7.2 ± 1.8 vs 7.1 ± 1.3 h, p = 0.77) and WASO (50 ± 46 vs 47 ± 30 min, p = 0.49) compared to NE. E showed higher Aix (26 ± 12 vs 14 ± 16, p = 0.006) and AP (11 ± 7 vs 7 ± 8, p = 0.03) than NE, in the presence of similar PWV, mean BP and heart rate (HR). In E group, Aix was related with height (r = -0.56, p = 0, 009), TST (r = -0.65, p = 0.002), while was not related with age, mean BP, PWV and HR. The association remained significant in a multiple regression model (beta = -2.92, p = 0.01), with TST accounting for 12.9% of Aix variance (r2 full model 0.84). In NE Aix was related with age (r = -0.82, p < 0.001), HR (r = 0.76, p < 0.001), TST (r = -0.49, p = 0.01), mean BP (r = 0.61, p = 0.01), PWV (r = 0.57, p = 0.004). The only independent determinants of Aix in NE were age (beta = 0.64, p = 0.02) and HR (beta = -0.37, p = 0.03). Conclusions: Central pressure augmentation is independently affected by sleep duration in individuals exposed to high levels of environmental aircraft noise.